Phenylpropanoids, Phenylalanine Ammonia Lyase and Peroxidases in Elicitor‐challenged Cassava (Manihot esculenta) Suspension Cells and Leaves - GÓMEZ‐VÁSQUEZ, ROCÍO (Ann Bot, 2004)
• Background and aims Control of diseases in the key tropical staple, cassava, is dependent on resistant genotypes, but the innate mechanisms are unknown. The aim was to study phenylpropanoids and associated enzymes as possible defence components. • Methods Phenylalanine ammonia‐lyase (PAL), phenylpropanoids and peroxidases (POD) were investigated in elicited cassava suspension cells and leaves. Yeast elicitor was the most effective of several microbial and endogenous elicitors. Fungitoxicity was determined against the cassava pathogens Fusarium solani, F. oxysporum and the saprotroph Trichoderma harzianum. • Key results A single and rapid (≥2–3 min) oxidative burst, measured as hydrogen peroxide, occurred in elicited cells. PAL activity was induced maximally at 15 h and was preceded by PAL mRNA accumulation, which peaked at 9 h. Symplasmic POD activity increased four‐fold in cells, 48 h post‐elicitation. POD isoforms (2–7 isoforms, pI 3·1–8·8) were detected in elicited and unelicited cells, extracellular medium and leaves but two extracellular isoforms were enhanced post‐elicitation. Also expression of a cassava peroxidase gene MecPOD1 increased in elicited cells. Only anionic forms oxidized scopoletin, with highest activity by isoform pI 3·6, present in all samples. Unidentified phenolics and possibly scopolin increased post‐elicitation, but there was no enhancement of scopoletin, rutin or kaempferol‐3‐O‐rutinoside concentration. Fungal germ tube elongation was inhibited more than germination by esculetin, ferulic acid, quercetin and scopoletin. T. harzianum was generally more sensitive than the pathogens and was inhibited by ≥50 µg mL(–1) of ferulic acid and quercetin and ≥10 µg mL(–1) of scopoletin. • Conclusions Phenolic levels in cells were not enhanced and were, theoretically, too low to be inhibitory. However, in combination and when oxidized they may contribute to defence, because oxidation of esculetin and scopoletin by peroxidase and of esculetin by tyrosinase enhanced their fungitoxicity up to 20‐fold.